2020
DOI: 10.1371/journal.pgen.1008682
|View full text |Cite
|
Sign up to set email alerts
|

Rare protein-altering variants in ANGPTL7 lower intraocular pressure and protect against glaucoma

Abstract: Protein-altering variants that are protective against human disease provide in vivo validation of therapeutic targets. Here we use genotyping data from UK Biobank (n = 337,151 unrelated White British individuals) and FinnGen (n = 176,899) to conduct a search for protein-altering variants conferring lower intraocular pressure (IOP) and protection against glaucoma. Through rare protein-altering variant association analysis, we find a missense variant in ANGPTL7 in UK Biobank (rs28991009, p.Gln175His, MAF = 0.8%,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 53 publications
(74 reference statements)
3
39
0
Order By: Relevance
“…We performed genetic association analyses of IOP and glaucoma across eight cohorts to identify rare and coding variants that modulate the risk for glaucoma through IOP. This led to the identification of ANGPTL7 as a candidate, consistent with findings reported recently by another group (19). In this report, we 1) strengthen the genetic link to glaucoma protection by (i) showing a consistent protective effect of the Gln175His variant in ANGPTL7 across eight cohorts, (ii) identifying a burden of ultra-rare missense variants in ANGPTL7 that reduce IOP levels, and (iii) identifying an additional rare ANGPTL7 loss-of-function variant in African-ancestry individuals; we also present 2) in vitro characterization of ANGPTL7 variants identified from genetic analyses; and 3) in vivo results showing that mice without Angptl7 have reduced basal IOP, and that even a partial knockdown of Angptl7 with siRNA can lead to lowering of IOP in mice.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…We performed genetic association analyses of IOP and glaucoma across eight cohorts to identify rare and coding variants that modulate the risk for glaucoma through IOP. This led to the identification of ANGPTL7 as a candidate, consistent with findings reported recently by another group (19). In this report, we 1) strengthen the genetic link to glaucoma protection by (i) showing a consistent protective effect of the Gln175His variant in ANGPTL7 across eight cohorts, (ii) identifying a burden of ultra-rare missense variants in ANGPTL7 that reduce IOP levels, and (iii) identifying an additional rare ANGPTL7 loss-of-function variant in African-ancestry individuals; we also present 2) in vitro characterization of ANGPTL7 variants identified from genetic analyses; and 3) in vivo results showing that mice without Angptl7 have reduced basal IOP, and that even a partial knockdown of Angptl7 with siRNA can lead to lowering of IOP in mice.…”
Section: Introductionsupporting
confidence: 90%
“…In this study, we present genetic and functional evidence for a role for ANGPTL7 in the physiological control of IOP and as a potential target for glaucoma therapy. Through genetic association analyses across 8 cohorts in Europeans, we confirmed the association of a rare missense variant, Gln175His (rs28991009), in ANGPTL7 with a decrease in IOP and with decreased risk for glaucoma (15,19). We further identified pLOF variants in ANGPTL7, Arg177* (rs143435072) and African ancestry-enriched Trp188* (rs145750805), that also associated with a decrease in IOP, suggesting that Gln175His carriers are protected from glaucoma through a loss or reduction in ANGPTL7 activity.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…These datasets enable the discovery of new disease genes with therapeutic potential at a large scale across phenotypes. For instance, a recent joint association analysis of the UK Biobank and the FinnGen study cohorts revealed rare variants in ANGPTL7 that protect against glaucoma (6). The UK Biobank is a collection of over 500,000 participants with standardized, detailed phenotypic data on which GWAS have been run extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown the utility of working with founder populations and population isolates to elucidate genetic variation for glaucoma [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] and other age-related ocular traits [ 26 , 27 , 28 , 29 ]. The Amish comprise an isolated, founder population that is culturally and genetically segregated from the general population of European descent [ 30 ].…”
Section: Introductionmentioning
confidence: 99%